Head in the clouds [large type] - Witemeyer, Karen (Thorndike Press, 2011)
Adelaide Proctor longs to find a real-life storybook hero to claim as her own. But when a husband-hunting debacle leaves her humiliated, she interviews for a governess position on a remote Texas sheep ranch and vows to leave her silly romantic yearnings behind. Gideon Wescott left his privileged life in England to make a name for himself in America's wool industry, never expecting to end up with a child. To his dismay, five-year-old Isabella hasn't uttered a word since she lost her mother. The unconventionality of the new governess concerns Gideon--and intrigues him at the same time. But he can't afford distractions. When Isabella's uncle comes to claim the girl--and her inheritance--Gideon and Adelaide must work together to protect Isabella from the man's evil schemes.